(untitled) (Research, Society and Development, 2021)
Folk medicine is the total of knowledge, skills, and healing practices from different cultures. In this context, this study aimed to identify the healers who use medicinal plants in their practices as well as carry out a socio-economic survey of these popular healing agents in the city of Guatambu (SC, Brazil). The survey was carried out in the rural and urban perimeter, using the snowball sampling technique, associated with a semi-structured questionnaire. As a result, the popular healing agents are mostly women (72%), with activities in agriculture (47%) and aged between 60 and 71 years (51%). Schooling pointed to elementary school (53%) and family constitution with the spouse (75%). The importance of religiosity in these activities was observed, mainly highlighted by the faith between those who practice and those who receive the blessing. The practice of blessing most of the time is applied to the treatment of muscle aches being applied generally, free of charge. Preparations based on medicinal plants are commonly produced by decoction, infusion, or syrups and help with family income. It was also verified the concern of the agents is not having someone to transmit their teachings at the end of life, due to the lack of interest of the younger people. This investigation contributes to the appreciation of the intangible culture and popular knowledge of the municipality, as well as to the understanding of the relationship of individuals with the environment and its importance in the conservation of biodiversity.